Treecat Wars - Weber, David 1952-; Lindskold, Jane M. (Riverdale, NY : Baen, 2013)
"Two young settlers on a pioneer planet seek to stop a war and to save the intelligent alien treecats from exploitation by unscrupulous humans"--
Keywords: Human-animal communication -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Space colonies -- Juvenile fiction; Human-animal communication -- Fiction; Human-animal relationships -- Fiction; Space colonies -- Fiction; Science fiction; Science fiction